Draft Annual Plan 2001-2002 State Planning Commission Tamil Nadu - Planning Commission (Planning Commission, 2001)
The formulation of the Annual Plan 2001-2002, the final year of the Ninth Five Year Plan, is focused on the policies and priorities of the new Government. the State's IX Plan outlay was at Rs.25,000 crores. During the first year of the plan, i.e. 1997-98, the expenditure was Rs.4,010 crores, against an approved outlay of Rs.4,004 crores. For 1998-99, against the plan outlay of Rs.4,500 crores, expenditure was Rs.4515.81 crores. an expenditure of Rs.5413.75 crores was incurred against the approved outlay of Rs.5250 crores in the Annual Plan 1999-2000. The revised outlay for the Annual Plan 2000-2001 was Rs.5775 crores which will be achieved without any shortfall. the approved outlays for the first four years has been Rs. 19504 crores which constitutes 78.16% of the IX Plan outlay. The following paragraphs give a brief review of the progress made in the crucial sectors of the economy during the year 2000-2001
State Planning Commission Tamil Nadu